Deregulation and productivity: selection or within-firm effect? - Oleksandr Shepotylo (European Regional Science Association (ERSA), 2014)
In the literature, trade liberalization increases industry productivity through two channels. First, firms increase productivity due to better and wider choice of inputs. In addition, at least theoretically, the mechanism of selection eliminates the least productive firms from the industry. To disentangle the sources of industry productivity increase, we apply the recently developed quantile approach (Combes et al., 2012) to the episode of trade and services liberalization in Ukraine. We modify the methodology in order to study changes in productivity distribution within an industry over time. We start with the Melitz model of an industry with heterogeneous firms. Unlike in the original model, we allow for productivity distribution to change over time as a result of deregulation. By looking at changes in productivity distribution of manufacturing and services firms in Ukraine in 2001-2009, we estimate the left-truncation, dilation, and shift in distribution for each NACE 2 digit sector. We compare relative importance of the within firm channel of productivity increase vis-à-vis the selection channel. We further relate the estimates of the left-truncation, dilation, and shift to industry measures of trade and services liberalization that include input tariffs liberalization and input services liberalization.
Keywords: 330; selection; productivity; distribution; quantile method